1996
DOI: 10.1891/0886-6708.11.3.213
|View full text |Cite
|
Sign up to set email alerts
|

The Cycle of Trauma: Relationship Aggression in Male Vietnam Veterans With Symptoms of Posttraumatic Stress Disorder

Abstract: This study examined the association between symptoms of Posttraumatic Stress Disorder (PTSD) in male Vietnam veterans and their use of aggressive behavior in relationships with intimate female partners. Fifty couples participated in the study. Veterans reported on their PTSD symptoms, and veterans and partners completed measures assessing the veterans’ use of physical, verbal,’ and psychological aggression during the preceding year as well as measures of their own perceptions of problems in the relationship. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(147 citation statements)
references
References 0 publications
9
133
5
Order By: Relevance
“…All studies were conducted in high-income countries, with seven in the USA [15,23,[41][42][43][44][45], one in Canada [46], one in Israel [47] and one in the UK [20]. Seven papers sampled only military veterans [15,23,41,42,44,45,47], two papers sampled only active-duty military personnel [43,46] and one sampled both active-duty and ex-service personnel [20].…”
Section: Key Featuresmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies were conducted in high-income countries, with seven in the USA [15,23,[41][42][43][44][45], one in Canada [46], one in Israel [47] and one in the UK [20]. Seven papers sampled only military veterans [15,23,41,42,44,45,47], two papers sampled only active-duty military personnel [43,46] and one sampled both active-duty and ex-service personnel [20].…”
Section: Key Featuresmentioning
confidence: 99%
“…US National Guard units, US Air Force, Canadian Regular Forces and UK Armed Forces communities). Six studies reported on past year violence only [15,23,[41][42][43]47], three on any violence perpetrated within a current relationship [44][45][46] and one on violence perpetrated in the weeks following return from deployment [48]. Six studies included both male and female military personnel and four included only men.…”
Section: Key Featuresmentioning
confidence: 99%
See 3 more Smart Citations